Santificado seja vosso tempo livre: a influência do catolicismo nas práticas de divertimento em Diamantina (1903 - 1930) - Ronaldo Flaviano de Souza Junior (2021)
This research proposes to discuss about the influence, on the part of the Catholic Church, regarding the practices of entertainment in the city of Diamantina, Minas Gerais, between the years 1903 to 1930. From the speeches of the newspapers circulating in the city, we sought to above all, to identify the main amusements of the time, choosing those that stood out in the sources so that from then on they could understand how they were developed and list the possible attempts to regulate these activities by the Church. In the analyzed texts, one can perceive a constant attempt at a moralizing education based on the activities developed with constant instructional notes in the journals, or even excerpts in which the way in which people developed or behaved during such practices were criticized. The choice of the city, in which Catholicism exercised significant influence in the most varied sectors of social life, made it possible to understand the dynamics of entertainment in a society that was undergoing significant technological transformations, coupled with the strong appeal for the Europeanization of customs and practices in which the individual passed stand out in the local urban scene.